Dose–response effects of resistance training on physical function in frail older Chinese adults: A randomized controlled trial - Xiaoxing Lai; Hongwei Zhu; Zhao Wu; Baoyu Chen; Qian Jiang; Hongdi Du; Xiaopeng Huo (Journal of Cachexia, Sarcopenia and Muscle, 2023)
Abstract Background Effective exercise for the frail elderly has been found to contribute to healthy aging; the corresponding relationship between intensity and volume of exercise and health effects remains unclear. The present study aimed to investigate the dose–response effects of resistance training on muscle strength and physical fitness in frail older adults. Methods In this randomized controlled trial, participants were randomized into seven groups: moderate‐volume low‐intensity, moderate‐volume moderate‐intensity, moderate‐volume high‐intensity, high‐volume low‐intensity, high‐volume moderate‐intensity, high‐volume high‐intensity and routine care, receiving 12 weeks of resistance training of different intensities and volumes of exercise. The outcomes were muscle strength (assessed by ergonomics force gauges) and physical fitness function (assessed by the 6‐min walking test [6MWT], the 30‐s sit‐to‐stand test [30sSTST] and the 8‐foot up‐and‐go test [8‐FUGT]) before and at 6 and 12 weeks of intervention. Results A total of 161 participants completed the exercise intervention. There were no significant differences in age, sex, height, body weight and body mass index among the seven groups. The exercise volume of resistance training showed linear relationships with muscle strength of the lower limbs, 30sSTST and 6MWT results and a non‐linear relationship with 8‐FUGT. Resistance training intensity was found to have a linear relationship with muscle strength of the lower limbs and 6MWT and non‐linear relationships with 30sSTST and 8‐FUGT. The mixed linear model analysis revealed that the lower limb muscle strength differed significantly before and during the intervention (W = 8571.5, Padj < 0.001), before and after the intervention (W = 6968, Padj = 0.001) and during and after the intervention (W = 2834.5, Padj < 0.001); that the 6MWT performance differed during and after the intervention (W = 3184, Padj < 0.001); and that the 30sSTST was different between before and during the intervention (W = 2350.5, Padj = 0.012) and between during and after the intervention (W = 2290.5, Padj = 0.045). Conclusions Resistance training was found to be associated with muscle strength and physical fitness in frail older adults in a dose‐dependent manner. High‐intensity resistance training could be more effective for improving the muscle strength of frail older adults, and the improvement of 6MWT performance was even higher. High‐volume resistance training significantly improved muscle strength, with even greater improvement in the 30sSTST and 6MWT performances. Both the intensity and volume of exercise were found to greatly value physical function in frail older adults. Low–moderate‐intensity resistance training and low–moderate‐volume resistance training also had some advantages in terms of safety, efficacy and acceptance in elderly with frailty.